NILAI MENGUTAMAKAN PELANGGAN DALAM KALANGAN KAKITANGAN DI IPTS: SATU TINJAUAN TERHADAP PELAKSANAAN PIAWAIAN MS 1900:2014: CUSTOMER PRIORITY VALUE AMONG STAFF IN PRIVATE UNIVERSITY: A SURVEY TOWARDS IMPLEMENTATION OF MS 1900:2014 STANDARD - Mohamed , Hasan Al-Banna bin; Ahmad, Azmi bin; Sahol Hamid, Norashikin binti; Basir, Siti Arni; Abdul Ghani Azmi, Ilhaamie (Online Journal of Islamic Management and Finance (OJIMF), 2022)
Nowadays, the appreciation of noble values in organizational management is emphasized when new working methods and norms are developing rapidly. The value aspect of prioritizing customers first is often an important topic to ensure that a product or service is competitive and excellent. Accordingly, an organization such as a higher education institution that involves many customers is very relevant in ensuring that the services provided are of high quality and ultimately provide satisfaction to all parties. Therefore, this study focuses on the appreciation of the noble values of prioritizing customers in a Private Institution of Higher Learning, Malaysia which has adopted the implementation of a Shariah-based Quality Management System (MS 1900: 2014). The methodology of this study uses a quantitative study design through data collection by survey method with the distribution of questionnaires using simple random sampling. The respondents of this study involved a total of 297 staff which includes academic staff, executive and non-executive staff. The results were analyzed through the IBM Statistical Package for Social Science (IBM SPSS) which engaged the Pearson Correlation Test, using descriptive and inferential analysis. Furthermore, the findings of the study have proven that there is a positive relationship between the noble value of prioritizing customers with aspects of job satisfaction among the staff involved. In conclusion, the findings of this study show that the appreciation of noble values of prioritizing customers has a significant relationship and influences the job satisfaction while implementing Shariah-based Quality Management System (MS 1900) in institutions of higher learning.